2012
DOI: 10.1074/jbc.m112.368548
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Riproximin Binding Properties Reveals a Novel Mechanism for Cellular Targeting

Abstract: Background: Riproximin is a cytotoxic lectin from Ximenia americana showing tumor selectivity. Results: Riproximin selectively binds to two types of glycoconjugates present on glycoproteins, cross-linking them by its two binding sites. Conclusion:The biologic activity of riproximin is determined by specific and dynamic interactions with multivalent, cancerrelated glycan targets. Significance: The selectivity of riproximin for cancer cells relies on its unique targeting mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…The clustered Tn antigen (repetitive N-acetyl-Dgalactosamine; GalNAc), a cancer-specific O-glycan on mucins, as well as bi-and tri-antennary complex N-glycan structures (NA2/NA3) were recently found to be molecules with potent binding affection to Rpx. 5 The latter finding, which includes a high affinity of Rpx for CEA, was basis to relate the expression levels of the CEACAM gene group to the respective cells' sensitivity toward Rpx. This gene group has been recognized to function in cancer progression, inflammation, angiogenesis, Table 1 and metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clustered Tn antigen (repetitive N-acetyl-Dgalactosamine; GalNAc), a cancer-specific O-glycan on mucins, as well as bi-and tri-antennary complex N-glycan structures (NA2/NA3) were recently found to be molecules with potent binding affection to Rpx. 5 The latter finding, which includes a high affinity of Rpx for CEA, was basis to relate the expression levels of the CEACAM gene group to the respective cells' sensitivity toward Rpx. This gene group has been recognized to function in cancer progression, inflammation, angiogenesis, Table 1 and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…We reasoned that it would be worth investigating 2 , and Martin R Berger the activity of Rpx in PDAC models, because a colorectal cancer liver metastasis model had shown explicit antineoplastic activity. 1 Moreover, the affinity of Rpx for carcinoembryonic antigen (CEA) 5 suggested that neoplasias expressing this glycoprotein might be preferential targets. Therefore, we determined the sensitivity of 17 PDAC cell lines to Rpx and investigated in a newly established PDAC liver metastasis model, whether Rpx has antineoplastic efficacy against PDAC cells growing in rat liver.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this cytotoxicity of Rpx against different cancer cell lines varied over a broad range (maximum by a factor of 100), which is possibly due to differential expression of receptors required for Rpx binding, specific molecular routes and nega-tive feedback mechanisms developed by the cancer cells over time. Nevertheless, Rpx illustrated specific toxicity towards tumor cell lines, whereas non-tumor cell lines showed either no or only a marginal sensitivity (16)(17)(18)(19). Further investigations on the antineoplastic potential of Rpx were accomplished in colorectal and pancreatic cancer liver metastasis rat animal models.…”
Section: Introductionmentioning
confidence: 99%
“…EHL shows specificity for N-acetyl-galactosamine [5,9], an overexpressed and incompletely glycosylated sugar in the Tn antigen which characterizes cancer linked O-glycans [12]. Other N-acetyl-galactosamine specific RIPs such as the Mistletoe lectin and Riproximin have demonstrated promising therapeutic relevance as anticancer agents [13][14][15]. EHL could thus have a promising future as an anticancer agent, if its toxicity can be harnessed and tuned to appropriate levels.…”
Section: Introductionmentioning
confidence: 99%